Efficient passivated phthalocyanine-quantum dot solar cells. Issue 9 (18th December 2014) - Blas-Ferrando, Vicente M.; Ortiz, Javier; González-Pedro, Victoria; Sánchez, Rafael S.; Mora-Seró, Iván; Fernández-Lázaro, Fernando; Sastre-Santos, Ángela
Abstract : The power conversion efficiency of CdSe and CdS quantum dot sensitized solar cells is enhanced up to 45% for CdSe and 104% for CdS by passivation with an asymmetrically disulfide substituted phthalocyanine. Abstract : The power conversion efficiency of CdSe and CdS quantum dot sensitized solar cells is enhanced by passivation with asymmetrically substituted phthalocyanines. The introduction of the phthalocyanine dye increases the efficiency up to 45% for CdSe and 104% for CdS. The main mechanism causing this improvement is the quantum dot passivation. This study highlights the possibilities of a new generation of dyes designed to be directly linked to QDs instead of the TiO2 electrodes.